2008
DOI: 10.4137/bmi.s834
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Biomarkers of Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia, or BPD, is a chronic pulmonary disorder of premature infants, commonly defi ned as having an oxygen requirement at 36 weeks postmenstrual age. It is an important source of morbidity and mortality in premature neonates. Its' etiology appears to be multifactorial with the most common associations being prematurity, need for mechanical ventilation, and oxygen exposure. Implied in the pathogenesis of BPD is the role of cytokines which are immune mediators produced by most cell types. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 62 publications
1
55
0
1
Order By: Relevance
“…1 A recent report has implicated HMGB1 in an animal model of chorioamnionitis. 19 Interestingly, both TNF-a and IL-1b, known to be early-release cytokines in response to injurious stimuli and potent inducers of the late-release cytokine HMGB1, have been implicated in animal models 20,21 and human 22 BPD. Although we were unable to locate any reports of HMGB1 in developmentally appropriate animal models of BPD, HMGB1 has been reported to mediate the inflammatory cascade in an experimental model of necrotizing enterocolitis in neonatal rats.…”
mentioning
confidence: 99%
“…1 A recent report has implicated HMGB1 in an animal model of chorioamnionitis. 19 Interestingly, both TNF-a and IL-1b, known to be early-release cytokines in response to injurious stimuli and potent inducers of the late-release cytokine HMGB1, have been implicated in animal models 20,21 and human 22 BPD. Although we were unable to locate any reports of HMGB1 in developmentally appropriate animal models of BPD, HMGB1 has been reported to mediate the inflammatory cascade in an experimental model of necrotizing enterocolitis in neonatal rats.…”
mentioning
confidence: 99%
“…Human neonates who developed BPD showed increased levels of tumor necrosis factor alpha (TNFα) in the tracheal aspirates [ 102 ]. Lung tissue of neonatal rat and mice pups exposed to hyperoxia also showed an increase in TNFα [ 15 ].…”
Section: Tumor Necrosis Factor Alphamentioning
confidence: 99%
“…This suppresses the secretion of cytokines and the ability of those cells to function as accessory cells for T-cell and NK-cell stimulation [ 97 ]. Serum and tracheal aspirate IL-10 levels were found decreased in those infants who developed BPD [ 102 ].…”
Section: Il-10mentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have identified an association between candidate gene variants and BPD. Most of these studies have focused on genes for innate immunity, antioxidant defenses, mechanism of vascular remodeling, and genes coding for surfactants proteins (5,10). While many significant findings have been reported, a majority of them have not been replicated in subsequent cohorts (5,6).…”
mentioning
confidence: 99%